1989
DOI: 10.1029/jb094ib12p17333
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and mechanisms of deformation around the Hellas and Isidis Impact Basins on Mars

Abstract: The distribution and age of early volcanic and tectonic features surrounding the Hellas and Isidis impact basins are shown to fit a four‐stage sequence. First, concentric “canyons” form outside the basin boundary scarp at or near the time of basin formation, followed shortly thereafter by radial troughs extending beyond the boundary scarp. After a hiatus, concentric graben develop inside the basin within the massif ring. Finally, soon after graben formation, widespread volcanic plains are emplaced between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
87
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(87 citation statements)
references
References 32 publications
0
87
0
Order By: Relevance
“…Based on the craterdiameter scaling relationships of Grieve and Cintala (1992), Clifford (1993) has estimated that the formation of a ∼1.5 × 10 3 km diameter impact basin will produce ∼10 7 km 3 of impact melt, the majority of which is expected to have pooled in the basin's interior. In addition, the intense fracturing of the underlying crust is likely to have focused considerable postimpact igneous activity in these locations (Schultz and Glicken 1979, Wichman and Schultz 1989, Tanaka and Leonard 1995. As a result, the lithology of the basin floors, as well as much of the surrounding terrain, may well be dominated by a combination of coherent igneous rock and rewelded breccias.…”
Section: Impact Basinsmentioning
confidence: 96%
“…Based on the craterdiameter scaling relationships of Grieve and Cintala (1992), Clifford (1993) has estimated that the formation of a ∼1.5 × 10 3 km diameter impact basin will produce ∼10 7 km 3 of impact melt, the majority of which is expected to have pooled in the basin's interior. In addition, the intense fracturing of the underlying crust is likely to have focused considerable postimpact igneous activity in these locations (Schultz and Glicken 1979, Wichman and Schultz 1989, Tanaka and Leonard 1995. As a result, the lithology of the basin floors, as well as much of the surrounding terrain, may well be dominated by a combination of coherent igneous rock and rewelded breccias.…”
Section: Impact Basinsmentioning
confidence: 96%
“…It formed approximately 4 Ga ago near the end of the Early Noachian (Wilhelms, 1973;Wichman and Schultz, 1989;Schultz and Frey, 1990;Ivanov et al, 2012). Gravimetry measurements suggest that the impact that formed Isidis Planitia may have thinned the underlying crust to as little as 3 km (Zuber et al, 2000;Neumann et al, 2004).…”
Section: Crustal Thickness and Geothermal Heat Fluxmentioning
confidence: 97%
“…Our interpretation is consistent with that of Melosh (1976), who described grabens generated by impact-related stress relaxation. In addition, Wichman and Schultz (1989) reported that some of these grabens are Hellas impact-induced, near-basin concentric canyons circular to the giant impact basin. These grabens are well defined with flat floors, and their western walls occur at higher elevations than their eastern walls (Figure 2 (a,b)).…”
Section: Grabensmentioning
confidence: 99%